The corporate sector and the current account - Jan Behringer; Till van Treeck (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2019)
In this paper, we analyze how corporate sector behavior has affected national current account balances in a sample of 25 countries for the period 1980-2015. A consistent finding is that an increase (decrease) in corporate net lending leads to an increase (decrease) in the current account, controlling for standard current account determinants. We disentangle the current account effects of corporate saving and investment and we explore a number of alternative explanations of our results, including incomplete piercing of the "corporate veil" by households, foreign direct investment activities, a temporary crisis phenomenon, and changes in income inequality. We conclude that corporate sector saving is an important driver of macroeconomic trends and that the rise of corporate net lending especially in a number of current account surplus countries has contributed considerably to global current account imbalances.
Keywords: D15; E21; F41; G35; 330; Corporate sector; sectoral financial balances; current account determinants